Investigation of the Possibility for Control of High-Temperature Synthesis of Nanomaterials; Materials Science Forum; Vol. 942 : Modern Problems in Materials Processing, Manufacturing, Testing and Quality Assurance - Sechin A. I. Aleksandr Ivanovich (2019, 2019)
Title screen